Characterization and insight mechanism of an acid-adapted β-Glucosidase from Lactobacillus paracasei and its application in bioconversion of glycosides - Xie, Yufeng; Yan, Xinrui; Li, Changzhuo; Wang, Shumei; Jia, Longgang (Frontiers in Bioengineering and Biotechnology, 2024)
β-glucosidase is one class of pivotal glycosylhydrolase enzyme that can cleavage glucosidic bonds and transfer glycosyl group between the oxygen nucleophiles.Lactobacillus is the most abundant bacteria in the human gut. Identification and characterization of new β-glucosidases from Lactobacillus are meaningful for food or drug industry. Herein, an acid-adapted β-glucosidase (LpBgla) was cloned and characterized from Lactobacillus paracasei. The recombinant LpBgla exhibited maximal activity at temperature of 30 °C and pH 5.5, and the enzymatic activity was inhibited by Cu 2+ , Mn 2+ , Zn 2+ , Fe 2+ , Fe 3+ and EDTA. The insight acid-adapted mechanism of LpBgla was investigated using molecular dynamics simulations. The LpBgla showed a more stable structure, wider substrate-binding pocket and channel aisle, more hydrogen bonds and stronger molecular interaction with the substrate at pH 5.5 than pH 7.5. Five residues including Asp45, Leu60, Arg120, Lys153 and Arg164 might play a critical role in the acid-adapted mechanism of LpBgla. Moreover, LpBgla showed a broad substrate specificity and potential application in the bioconversion of glycosides, especially towards the arbutin. Our study greatly benefits for the development novel β-glucosidases from Lactobacillus, and for the biosynthesis of aglycones.